Educational Implications of Group Dynamics - Misra, Vinod; Tyagi, Ritu (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Group dynamics is concerned with the study of techniques and procedures for affecting the structure of behavior of a social group. Thus in group-dynamics changes are brought in the behavior pattern of its members. Groups have an attribute that can affect its structure, objectives and activities. If a change takes place in favors of one aspect, it also affects other aspects. The change occurring in a group is called by the name of dynamic. A good teacher always keeps an eye on factors affecting group dynamics for better development of the personality of his students. The paper focuses on the educational implications of group dynamics.